2024
DOI: 10.2174/0115733998274599231109034741
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy Leading to Blindness- A Review

Amandeep Kaur,
Ranjeet Kumar,
Amit Sharma

Abstract: Diabetic retinopathy (DR) is the most common microvascular complication of diabetes that damages the retina, leading to blindness. People with type 1 diabetes are at greater risk of developing DR than people with type 2 diabetes. Diabetic retinopathy may be divided into two primary categories: proliferative diabetic retinopathy (PDR) and non-proliferative diabetic retinopathy (NPDR). There are multiple risk factors for the onset and progression of diabetic retinopathy, such as hypertension, obesity, smoking, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Students and employed patients in our study showed a signi cantly better attitude towards diabetic foot care than unemployed ones. Having a job typically leads to higher income and potentially exposure to information related to better diabetic foot care practices which could translate into a more positive and clear attitude towards managing diabetes and diabetic foot care (4).…”
Section: Discussionmentioning
confidence: 99%
“…Students and employed patients in our study showed a signi cantly better attitude towards diabetic foot care than unemployed ones. Having a job typically leads to higher income and potentially exposure to information related to better diabetic foot care practices which could translate into a more positive and clear attitude towards managing diabetes and diabetic foot care (4).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of pericytes and endothelial cells changes the architecture of the capillary vessels and causes microaneurysms within the retina, deterioration of the blood-retinal barrier, and retinal ischemia. Over time, retinal ischemia leads to the upregulation of angiogenic factors, such as the vascular endothelial Biomolecules 2024, 14, 525 2 of 14 growth factor (VEGF), and the downregulation of anti-angiogenic factors, such as the pigment epithelium-derived factor [2,5,6]. Increased VEGF signaling is strongly associated with increased vascular permeability via the breakdown of tight junctions, resulting in the leakage of blood and exudates from the retinal microvasculature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-induced retinal vessel growth characterizes several pathological and degenerative diseases of the retina among which retinopathy of prematurity (ROP) is characterized by abnormal vascularization as a consequence of preterm birth ( Pascarella et al, 2024 ). Among neovascular diseases of the adult, proliferative diabetic retinopathy (PDR) is the more advanced stage of DR that is characterized by thin and weak blood vessels whose bleeding can cause scar tissue leading to retinal detachment ( Kaur et al, 2024 ). In addition, neovascular age-related macular degeneration (nAMD) involves abnormal proliferation of choroidal vessels, which enter into the subretinal space through the Bruch’s membrane.…”
Section: Introductionmentioning
confidence: 99%